Architectural form manufacturing techniques (Journal of the College of Basic Education, 2022)
Architecture is one of the important products of the era, which helped man to contain his activities, and it has evolved over time as a result of the development of all related fields, which help to establish an architectural form in its final form. Through his vision of his new needs with the change of time affecting the statement of the role of specialized technology to serve man